Cardiac structure and function in schizophrenia: a cardiac MR imaging study - Osimo,E; Brugger,S; De,Marvao A; Pillinger,T; Whitehurst,T; Statton,B; Quinlan,M; Berry,A; Cook,SA; O'Regan,D; Howes,OD (British Journal of Psychiatry, 2020)
Background: Heart disease is the leading cause of death in schizophrenia. However, there has been little research directly examining cardiac function in schizophrenia.Aims:We investigated cardiac structure and function in patients with schizophrenia using cardiac magnetic resonance imaging (CMR) after excluding medical and metabolic comorbidity. Methods:80 participants underwent CMR to determine biventricular volumes and function and measures of blood pressure, physical activity, and glycated haemoglobin levels. Patients and controls were matched for age, sex, ethnicity, and body surface area. Results:Patients with schizophrenia had significantly smaller indexed left ventricular (LV) end-diastolic volume (effect size, d=-0.82, p=0.001), LV end-systolic volume (d=-0.58, p=0.02), LV stroke volume (d=-0.85, p=0.001), right ventricular (RV) end-diastolic volume (d=-0.79, p=0.002), RV end-systolic volume (d=-0.58, p=0.02), and RV stroke volume (d=-0.87, p=0.001) but unaltered ejection fractions relative to controls. LV concentricity (d=0.73, p=0.003) and septal thickness (d=1.13, p<0.001) were significantly larger in schizophrenia. Mean concentricity in patients was above the reference range. The findings were largely unchanged after adjusting for smoking and/or exercise levels and were independent of medication dose and duration. Conclusions:Patients with schizophrenia show evidence of concentric cardiac remodelling compared to healthy controls of a similar age, sex, ethnicity, body surface area and blood pressure, and independent of smoking and activity levels. This could be contributing to the excess cardiovascular mortality observed in patients. Future studies should investigate the contribution of antipsychotic medication to these changes.